Technical change, prices and factor demand: Fertilizers in Argentine Agriculture - Gallacher, Marcos (Instituto de Economía y Finanzas. Facultad de Ciencias Económicas. Universidada Nacional de Córdoba., 2022)
The objective of this paper is to analyze the relative importance of technical change and input prices in explaining factor demand in Argentine agriculture. Motivation for the paper is the fifteen-fold increase in fertilizer demand observed in Argentina in the 1990-2019 period. Results show that in the 1990 – 2019 period increase in fertilizer demand was a result not only of a fall in the fertilizer/crop price ratio, but also on increased marginal productivity of the fertilizer input. It is suggested that this is a result of the increased importance of “knowledge inputs” in the production process. Reception date: 24/03/2022 Acceptance date: 22/08/2022